The L2-Alexander torsion of 3-manifolds. (27th July 2016) - Dubois, Jérôme; Friedl, Stefan; Lück, Wolfgang
Abstract : We introduce L^2 -Alexander torsions for 3-manifolds, which can be viewed as a generalization of the L^2 -Alexander invariant of Li–Zhang. We state the L^2 -Alexander torsions for graph manifolds and we partially compute them for fibered manifolds. We furthermore show that, given any irreducible 3-manifold there exists a coefficient system such that the corresponding L^2 -torsion detects the Thurston norm.